A method to measure dynamic dorsal foot surface shape and deformation during linear running using digital image correlation - Blenkinsopp, R.; Harland, A.; Price, D.; Lucas, T.; Roberts, J. (Procedia Engineering, 2012)
This paper reports a methodology that employs a three dimensional (3D) digital image correlation (DIC) system to measure dynamic foot shape during running. DIC is a non-contact optical measurement system, capable of high resolution surface deformation measurements derived from digital images captured of a surface undergoing a deformation. The methodology presented in this paper uses a plurality of synchronised high speed cameras to capture images of the stance phase of the gait cycle, from which surface shape and deformation measurements can be made. Results related to foot morphology are presented which show the merit of the method and potential for future use.